Biosynthesis of Glucosyl Diglycerides by Mycoplasma laidlawii Strain B - Smith, Paul F. (1969)
Monoglucosyl diglyceride is synthesized from 1,2-diglyceride and uridine-5′-diphosphoglucose (UDP); diglucosyl diglyceride from monoglucosyl diglyceride, and uridine-5′-diphosphoglucose by membranes of Mycoplasma laidlawii strain B. All of these enzymatic activities reside in the membrane. Membranes solubilized by detergent action or succinylation and acetone powders of membranes were inactive. Requirements for Mg(2+), UDP, and appropriate lipid acceptor were demonstrated for biosynthesis of both glycolipids. Glucose-1-phosphate plus uridine triphosphate could replace the UDP requirement. A medium of relatively high ionic strength and a critical concentration of sodium lauryl sulfate stimulated biosynthesis of the monoglucosyl diglyceride. The optimal pH for both reactions was 8.0. A specificity for 1,2-diglyceride from the homologous organism was found for optimal synthesis of the monoglucosyl diglyceride, and a specificity for monoglucosyl diglyceride was found in the case of diglucosyl diglyceride synthesis. Both reactions were specific for UDP.